Tethered aminohydroxylation (TA) reaction of amides. - Donohoe, T; Callens, C; Thompson, A (2009)
The first examples of amide-tethered aminohydroxylation reactions, catalyzed by osmium, showing that the use of N-O-based reoxidants are essential for success, are reported. The system that is described is compatible with a variety of different alkene substitution patterns and ring sizes and works with low loadings in both cyclic and acyclic systems. The levels of diastereoselectivity that were observed for substituents at both the allylic and homallylic position bode well for the use of stereoselective TA reactions in organic synthesis.